2018
DOI: 10.3390/diagnostics8030051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Functional Connectivity Alterations in Autism Spectrum Disorder Using Network-Based Statistics

Abstract: The study of resting-state functional brain networks is a powerful tool to understand the neurological bases of a variety of disorders such as Autism Spectrum Disorder (ASD). In this work, we have studied the differences in functional brain connectivity between a group of 74 ASD subjects and a group of 82 typical-development (TD) subjects using functional magnetic resonance imaging (fMRI). We have used a network approach whereby the brain is divided into discrete regions or nodes that interact with each other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
(49 reference statements)
2
12
0
4
Order By: Relevance
“…Similar to our results, another study [Chen, Kang, & Wang, ] found no significant difference in SFC between the ASD and TD groups after FDR correction based on the AAL template. Meanwhile, they also found that the mean maps of SFC [Chen et al, ; Iidaka, ; Pascual‐Belda et al, ] were similar between the ASD and TD groups, which is in line with our findings. More importantly, other factors such as heterogeneous samples and different preprocessing methods could also lead to inconsistent findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our results, another study [Chen, Kang, & Wang, ] found no significant difference in SFC between the ASD and TD groups after FDR correction based on the AAL template. Meanwhile, they also found that the mean maps of SFC [Chen et al, ; Iidaka, ; Pascual‐Belda et al, ] were similar between the ASD and TD groups, which is in line with our findings. More importantly, other factors such as heterogeneous samples and different preprocessing methods could also lead to inconsistent findings.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, differences in the available multiple comparison methods could also explain this variation. Notably, the most significant results [Chen et al, ; Pascual‐Belda, Diaz‐Parra, & Moratal, ; Supekar et al, ] were found in SFC based on an AAL atlas using a network‐based statistic (NBS) approach [Zalesky, Fornito, & Bullmore, ]. This might be due to the fact that FDR correction is more conservative than NBS, especially when the range of connection is large under a low threshold ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Algunos autores sugieren que los niños con TEA muestran un patrón de activación típico con una sobreactivación en aquellos circuitos estructural y funcionalmente más «primitivos» y una falta de conectividad en aquellos cuyo desarrollo es más prolongado en el tiempo, e implican estructuras y respuestas más racionales 21 .…”
Section: Exceso De Conexiones Localesunclassified
“…En este sentido se ha hallado una disminución de las conexiones neurales llevadas a cabo por el sistema límbico, tálamo y cerebelo, sugiriendo una alteración en la maduración del cerebro 21 . El tálamo en conexión con el lóbulo frontal desempeña un papel importante en funciones cognitivas como la memoria y la atención.…”
Section: Subconectividad a Larga Distanciaunclassified
“…have been reported to be affected in ASD (Hampson and Blatt, 2015;Maximo and Kana, 2019;Pascual-Belda, et al, 2018). Among these brain regions involving in ASD, the cerebellum was one of the most studied brain regions.…”
Section: Introductionmentioning
confidence: 99%